Designing a Zero Trust Architecture for Securing API Gateways in Digital Banking Systems - Sitorus, Riama Santy; Hutagaol, B. Junedi (Journal of Information Systems and Informatics, 2025)
In the era of digital banking transformation, Application Programming Interfaces (APIs) are essential for system integration and customer-facing innovations but also increase exposure to cyber security risks such as credential theft, API abuse, data breaches, and unauthorized access. This research proposes a conceptual Zero Trust Architecture (ZTA) model specifically designed to secure API Gateways in digital banking systems. Adopting a conceptual design methodology comprising literature review, component identification, architectural modelling, standards-based evaluation, and recommendation development the study introduces a framework that integrates core Zero Trust principles. Strong identity verification counters credential misuse, dynamic access control mitigates unauthorized access, encryption protects sensitive financial data, continuous monitoring identifies abnormal traffic, and real-time behavioral analytics prevents API abuse. Each component is mapped to relevant industry standards, ensuring resilience and regulatory compliance. Beyond the conceptual design, the findings highlight practical implications: applying ZTA at the API Gateway strengthens cyber security defenses against modern API threats, supports regulatory readiness, and provides banks with a structured roadmap for secure digital services. The study concludes that the proposed model delivers a comprehensive foundation for secure API communication in digital banking and actionable guidance for future implementation and research.
Keywords: Access control; API Gateway; Cyber Security; Digital Banking; Zero Trust Architecture